Technology - Based Business Idea Blueprint Shopping Trolley With Tracker / Nur Ai’n Jamil - Jamil, Nur Ai’n (2020)
Ain’s Trolley is located at Precint 15, Putrajaya near the Mydin Bazar. This company is a sole proprietorship company and focusing on producing and selling the trolley. Ain’s Tolley main production is trolleyOur company produces trolley for shopping or groceries purposes. Shopping trolley WITH tracker is the new innovation that can easily help people while doing groceries. People can scan the price on the trolley and the price will shown on the screen since it have a scanner on it. Besides, people can budget their spending on this trolley since it have a budgeting system. Then, this new innovation trolley can easily locate the desired product since it have a navigation system.